Efficacy and safety of intranasal insulin on postoperative cognitive dysfunction in elderly patients after laparoscopic radical resection of colorectal cancer: a double-blind pilot study - Zhang, Hailong; Zhao, Liqin; Li, Min; Li, Xu; Li, Ruofan; Wu, Di (Frontiers in Aging Neuroscience, 2024)
Objective: To evaluate the efficacy and safety of intranasal insulin on postoperative cognitive dysfunction (POCD) in elderly patients after laparoscopic radical resection of colorectal cancer. Methods: Older patients scheduled for laparoscopic radical resection of colorectal cancer at Beijing Luhe Hospital, Capital Medical University, between August 2023 and November 2023, were enrolled in this double-blind pilot study. Patients were randomized to the control and insulin groups at a 1:1 ratio. The primary outcome was the rate of POCD at postoperative 7 days. Results: A total of 61 patients (30 in the insulin group) were analyzed. The insulin group had a significantly lower POCD rate compared with the control group at postoperative day 7 [4(13.3%) vs. 12 (38.7%), P=0.024]. The serum levels of IL-6, TNF-α and S100β at T2-5 in the insulin group were significantly lower than those of the control group (IL-6: mean difference at T2, -4.14, P=0.036; T3, -3.84, P=0.039; T4, -3.37, P=0.013; T5, -2.57, P=0.042; TNF-α: mean difference at T2, -3.19, P=0.002; T3, -2.35, P=0.028; T4, -2.30, P=0.019; T5, -1.96, P=0.0181; S100β: mean difference at T2, -8.30, P=0.019; T3, -23.95, P=0.020; T4, -20.01, P=0.023; T5, -17.67, P=0.010). No insulin allergic reactions, nasal irritation, or hypoglycemic reactions were observed in either of the groups. Conclusion: Intranasal insulin may decrease the risk of POCD and inhibit the elevated serum IL-6, TNF-α, and S100β levels in elderly patients after laparoscopic radical resection of colorectal cancer, which proves that intranasal insulin may be a promising therapeutic option for POCD.